Investigasi terhadap Intensi Karier Mahasiswa Akuntansi - Dina Octavia Ellisabet; Sinarti Sinarti (Politeknik Negeri Batam, 2020)
This study aims to assist accounting students in pursuing their careers as accountants. This study discusses the research objectives which examine and analyze the sex and year of study, internship experience, anticipated interest and conflict (X) as variables that influence and development intentions (Y) as variables that are questioned. The data collection method used is by submitting a questionnaire involving accounting students in the Batam area. Respondents in the study were accounting students from second to fourth year in the 2019 school year. Data analysis in this study used multiple linear regression hypothesis tests. The results found that gender and years of study and internship experience influenced student career intentions. This shows that the higher level of class in male and female students will affect career intentions and students who have undergone an internship have a higher commitment.